Editorial: Literature and Philosophy in Schools - Alan Tapper; Raymond Driehuis (Journal of Philosophy in Schools)
Why study literature in schools? What special benefits come with an education in literature? What might students be missing if they bypass literature? These, surely, are hard questions. Will students who lack experience of literature lack imagination? Or human sympathies? Or moral development? Or cultural and historical awareness? Scratch the surface, and the questions about the value of literature as a school subject unfold rather rapidly, and dauntingly.